MAXIMIZING THE COLLECTION AND DISTRIBUTION OF ZAKAT AND INFAQ (A CASE STUDY ON LAZ ZAKAT SUKSES) - Muhammad Fathoni Yasin; Nur Aini; Ratna Yulika Go (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: Indonesia possesses a significant potential for Zakah, yet the collected amount currently only reaches around 4.3%. This requires a diligent and dedicated effort to continuously enhance the growth of the collection, one of which is through the management strategy of Zakat Institutions. This research focuses on LAZ Zakat Sukses, the Best City-level LAZ at the National level with outstanding performance. Methods: This study aims to ascertain the internal and external factors held by the institution and determine the most appropriate strategy to maximize its performance achievements. Employing a qualitative descriptive research method involving internal and external analysis, this research utilizes matrices such as IFE, EFE, SWOT, IE, BCG, and QSPM. Results: The findings of this research indicate that the most suitable strategy for this Institution based on its current fundamental conditions is Market Development. Market development is a strategy aimed at expanding the organization's reach by entering new markets or segments with existing products or services. Conclusion and suggestion: Particularly expanding into new territories, is a promising direction for Zakat Sukses. Key points and actions to consider when implementing this strategy are Geographical Expansion, Strategic Partnerships, Strengthen Volunteer Network, Synergy and Collaborative Programs, Digital Platform Expansion, Fundraising and Program Distribution, Monitoring and Evaluation, Communication and Outreach, Risk Management, Sustainability. Successful market development and expansion require careful planning, strong execution, and adaptability to changing circumstances.